Routine inflammatory markers are elevated in myelodysplastic syndromes at presentation - Howard Oster; Ekaterina Sklyar; Noa Golsdshmidt; Moshe Mittelman (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Immune and inflammatory processes have known contributions to the pathogenesis of myelodysplastic syndromes (MDS). The use of inflammatory markers, minimally used in current practice, is examined.